Stress Management - Ghosh, Manika (Ushus Journal of Business Management, 2021)
The opportunities in the new millennium is closely associated with the challenges in the work place not, only to excel but to maintain the optimum level of efficiency. This article highlights the consequences of stress at the work place and hence the need for both the employees and the management to ensure a healthy relationship within the organisation.